Tratamento de drenagem ácida sintética de mina em reator UASB: fontes de carbono e cargas de sulfato - Pereira , Luiz Francisco Fernandes (2017)
The aim of this study was to avalie the influence of three carbon source (ethanol, sucrose and whey) in the treatment of artificial acid mine drainage (AAMD), under acid conditions, sulfate and metal concentrations (copper, iron and zinc). Therefore, were used three anaerobic sludge blanket reactor (UASB), denominated RET, RSA and RSO, with carbon sources ethanol, sucrose and whey, respectively. The step 1, start-up of reactors, objected provide the gradual adaptation of the biomass in operational conditions, was for 371 days and composed of six phases. The results and operational characteristics of Phases 1 and 2 suggested the predominance of methanogenesis in both reactors, with removals of COD close to 90% and sulfate of less than 40%. After the establishment of the ratio COD/ sulfate = 2, from Phase 3, there was a significant modification in sulfate removal and dissolved sulfide total concentration in all reactors. For Phase 4, the drainage pH was corrected to 3.5. The results suggested the possible establishment of incomplete oxidized sulfate-reducing bacteria. For RET and RSA there was increase in the reduction of sulfate to sulfide, but with less efficiency in the removal COD and accumulating acids. The COD and sulfate removal was, respectively, for RET (78.2 ± 17.3) % and (76.1 ± 6.8) %, and for RSA (35.7 ± 3.8) % and (77.6 ± 5.3) %. On the other hand, for RSO, COD and sulfate removal were high, respectively, (88.3 ± 7.3) % and (71.0 ± 14.5) %. In Phases 5 and 6, 50 mgFe2 +.l-1 and 75 mgFe2 +.l-1 were inserted, respectively, under pH 3.3. The addition of the iron II seems to have been detrimental to RET and RSA, for the removal of COD and sulfate, reducing alkalinity and effluent pH. Due to operational problems in the RSO reactor, 50 mgFe2 + .l-1 was added in Phase 6, but the addition of the metal ion seems to have favored the system, in the several parameters analyzed. The Step 2, aimed at subjecting the reactors to increasing sulfate loads. It was started with the insertion of 100 mgFe2 +.l-1, under ration COD / sulfate = 2 and pH 3.3 and had a total duration of 129 days. The reactors were analyzed under increasing sulfate loading: 500 mg.l-1 (Phase 1), 1000 mg.l-1 (Phase 2) and 2000 mg.l-1 (Phase 3). The RET presented gradual adaptation to the iron II, reached efficiency approximately 100% for iron and sulfate removal 50%. The RSA reactor, didn’t sulfate removal after iron II additional and can’t meet the legal limits to wastewater discharged. The RSO reactor presented the best performance. For Phases 1 and 2, it showed approximately 70% efficiency for sulfate removal and COD removal above 80%. However, in Phase 3, there was an efficiency decrease to 48% of COD removal and 32% of sulfate.